2023
DOI: 10.1002/cam4.5910
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury indicators and subsequent cancer development among non‐fatty liver population

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Transcatheter arterial chemoembolization was included into the nonsurgical group. 40,41 Furthermore, given prior research that reported the predictive utility of the FIB-4 score for non-HCC cancers, [42][43][44] we also conducted further investigations to assess the ability of the FIB-4 in predicting breast cancer and colorectal cancer.…”
Section: Identification Of Hcc and Non-hcc Cancer Casesmentioning
confidence: 99%
“…Transcatheter arterial chemoembolization was included into the nonsurgical group. 40,41 Furthermore, given prior research that reported the predictive utility of the FIB-4 score for non-HCC cancers, [42][43][44] we also conducted further investigations to assess the ability of the FIB-4 in predicting breast cancer and colorectal cancer.…”
Section: Identification Of Hcc and Non-hcc Cancer Casesmentioning
confidence: 99%